USE OF TECHNOLOGY OF PRECISION CASTING INTO DISPOSABLE CERAMIC MOLD FOR PRODUCTION OF SHAPED CASTINGS AND OF CASTINGS WITH THE HIGHER PERFORMANCE REQUIREMENTS - B. I. Uvarov; P. E. Lushchyk; A. A. Andrits; L. P. Dolgiy; A. V. Zablotskiy (Литьë и металлургия, 2017)
Through the example of production of specific castings the effectiveness of the precision ceramic molding technology for the production of shaped castings and castings with the higher performance requirements has been demonstrated.